The Role Of The Provincial Representative Ombudsman Bengkulu In Preventing Maladministration In The City Of Bengkulu - Dita Nurhaiza; Evi Lorita; Antonio Imanda (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the Role of the Ombudsman Representative of Bengkulu Province in Preventing Maladministration in Bengkulu City. The method used in this research is descriptive qualitative research method. Furthermore, data collection techniques are carried out by conducting in-depth interviews, observation and documentation. After the data is obtained, the results of the research are further analyzed by means of data reduction, data presentation and drawing conclusions. The number of informants in this study was 4 people consisting of 2 key informants from the Ombudsman and 2 key informants from the Ombudsman Network. This research uses role theory according to Biddle and Thomas where there are several aspects in this research so that it can be seen that the one who prevents maladministration in the Ombudsman is the Prevention Assistant field assisted by other fields. implemented based on the target set by the central Ombudsman which focuses on government regulations and policies that must be implemented by public service providers, especially in Bengkulu City. The Ombudsman conducts outreach twice a year and continues to strive to supervise in order to prevent maladministration. Due to the Covid-19 pandemic the Ombudsman has conducted more socialization to social media such as Facebook, Instagram and Twitter, but what happens is there are still reports of maladministration from the public. Based on the results of the study, it is concluded that the role of the Omudsman in preventing maladministration in Bengkulu City has been consistently carried out based on legislation, namely Law No.25 of 2009 concerning public services.